2022
DOI: 10.1152/ajpregu.00259.2021
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-21 improves insulin action in nonlactating ewes

Abstract: During metabolically demanding physiological states, ruminants and other mammals coordinate nutrient use among tissues by varying the set point of insulin action. This set point is regulated in part by metabolic hormones with some antagonizing (e.g., growth hormone and TNFa) and others potentiating (e.g., adiponectin) insulin action. Fibroblast growth factor-21 (FGF21) was recently identified as a sensitizing hormone in rodent and primate models of defective insulin action. FGF21 administration, however, faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
3
0
2
Order By: Relevance
“…Despite not measuring plasma and tissue ceramides, chronic FGF21 infusion did not affect indices of adiponectin production in lactating dairy cows, including plasma adiponectin and adiponectin mRNA abundance (141). In contrast, Lamb et al (142) observed that FGF21 administration increased plasma adiponectin but did not affect plasma C16:0-and C24:0-ceramide and total ceramides in nonlactating ewes. Therefore, whether the FGF21-adiponectinceramide axis is present in early-lactation dairy cows experiencing NEB remains a matter for further research.…”
Section: Are Ceramides Predictive Markers Of Transition Cows' Health?mentioning
confidence: 85%
See 2 more Smart Citations
“…Despite not measuring plasma and tissue ceramides, chronic FGF21 infusion did not affect indices of adiponectin production in lactating dairy cows, including plasma adiponectin and adiponectin mRNA abundance (141). In contrast, Lamb et al (142) observed that FGF21 administration increased plasma adiponectin but did not affect plasma C16:0-and C24:0-ceramide and total ceramides in nonlactating ewes. Therefore, whether the FGF21-adiponectinceramide axis is present in early-lactation dairy cows experiencing NEB remains a matter for further research.…”
Section: Are Ceramides Predictive Markers Of Transition Cows' Health?mentioning
confidence: 85%
“…In contrast, Lamb et al. ( 142 ) observed that FGF21 administration increased plasma adiponectin but did not affect plasma C16:0- and C24:0-ceramide and total ceramides in nonlactating ewes. Therefore, whether the FGF21-adiponectin-ceramide axis is present in early-lactation dairy cows experiencing NEB remains a matter for further research.…”
Section: Can Adiponectin or Fgf21 Alter Ceramides Of Dairy Cows?mentioning
confidence: 87%
See 1 more Smart Citation
“…Die Diskrepanz zwischen den Befunden bei monogastrischen Tieren (und des Menschen) und Kühen haben Lamb et a. [79] bei nicht laktierenden Schafen geprüft. In diesen Versuchen werden die Widersprüche zwischen Wiederkäuern und Nicht-Wiederkäuern auf die Glukose-und NEFA-Konzentration und auf die Insulinsensitivität nicht beobachtet.…”
Section: Fibroblast Growth Factor 21 (Fgf21)unclassified
“…In diesen Versuchen werden die Widersprüche zwischen Wiederkäuern und Nicht-Wiederkäuern auf die Glukose-und NEFA-Konzentration und auf die Insulinsensitivität nicht beobachtet. Lamb et al [79] vermuten die Möglichkeit einer FGF21-Resistenz als Folge der Laktation. Wenn das bei Kühen p.p.…”
Section: Fibroblast Growth Factor 21 (Fgf21)unclassified